Functional traits driving pollinator and predator responses to newly established grassland strips in agricultural landscapes. Issue 8 (23rd May 2021) - Maas, Bea; Brandl, Manuela; Hussain, Raja Imran; Frank, Thomas; Zulka, Klaus Peter; Rabl, Dominik; Walcher, Ronnie; Moser, Dietmar
Abstract: Agricultural biodiversity and associated ecosystem functions are declining at alarming rates due to widespread land use intensification. They can only be maintained through targeted landscape management that supports species with different habitat preferences, dispersal capacities and other functional traits that determine their survival. However, we need better understanding whether short‐term measures can already improve functional diversity in European agroecosystems. We investigated spatio‐temporal responses of bees (solitary bees, bumblebees and honey bees), hoverflies, carabid beetles and spiders to newly established grassland strips in Lower Austria over 3 years, and along a distance gradient to old grasslands. Specifically, we asked if new grasslands, compared to old grasslands and cereal fields, serve as temporal dispersal habitat or corridor, and how species‐specific traits affect dispersal patterns. Using a trait‐based functional diversity approach, we investigated year and distance effects for nine selected key traits per taxon (e.g. body size, feeding guild and habitat preferences). Our results show that the functional diversity of predators and pollinators (i.e. functional richness and evenness), as well as community‐weighted means of selected key traits in new grasslands significantly differed from adjacent cereal fields, but only slowly adjusted to adjacent old grasslands. These effects significantly decreased with increasing distance to old grasslands for carabids and spiders, but not for mobile bees and hoverflies. Synthesis and applications . Over 3 years, newly established grassland strips supported larger sized and actively foraging/hunting species in the agricultural landscape. Adjacent crops likely benefit from such measures through enhanced functional diversity and related ecosystem services. However, our results also suggest that 3‐year period is too short to enhance the occurrence of pollinators and epigeic predators in new grasslands. Agri‐environment measures need to be complemented by the conservation of permanent habitats to effectively maintain species and functional diversity. Our findings should be acknowledged by European policy and agricultural decision makers for the design of more effective agri‐environment schemes, taking into account trait‐dependent species responses to land use change. Abstract : Over 3 years, newly established grassland strips supported larger sized and actively foraging/hunting species in the agricultural landscape. Adjacent crops likely benefit from such measures through enhanced functional diversity and related ecosystem services. However, our results also suggest that 3‐year period is too short to enhance the occurrence of pollinators and epigeic predators in new grasslands. Agri‐environment measures need to be complemented by the conservation of permanent habitats to effectively maintain species and functional diversity. Our findings should be acknowledged by European policy and agricultural decision makers for the design of more effective agri‐environment schemes, taking into account trait‐dependent species responses to land use change.